Effect of easily biodegradable amendments on heavy metal solubilization and accumulation in technical crops ‐ a field trial - Shilev, Stefan; Naydenov, Mladen; Tahsin, Nurettin; Sancho, Enrique D.; Benlloch, Manuel; Vancheva, Ventsislava; Sapundjieva, Krasimira; Kuzmanova, Jordanka (Journal of Environmental Engineering and Landscape Management, 2007)
Heavy‐metal soil pollution is a common environmental problem all over the world. In the induced phytoextraction process plants can transport and translocate to their above‐ground tissues significant concentration of contaminants. Since some heavy metals are mostly presented in non‐soluble state, the application of chelating agents is needed. In this study we introduced into the rhizosphere of maize (var. Kneja 530) and sunflower (var. Favorit) plants 1 and 5 mmol l−1 of EDDS and NTA, and 5 g kg−1 of nutrients to enhance the accumulated concentrations of cadmium, lead and zinc. The fraction of CaCl2‐extractable metals increased incrementing the concentration of chelates. This was clearly pronounced for all the metals in the treatments with NTA and for Pb in those with EDDS. Generally, under all the experimental conditions the accumulated heavy‐metal concentrations were found to be significantly higher than in the control. Thus, in the case of higher concentration of NTA and EDDS, the accumulated Cd in the leaves of sunflower was found to be threefold higher. The highest accumulation of Pb in the leaves of maize was observed when nutrients were added (62 mg kg−1). On the other hand, negative effects of the used chelating agents on soil bacteria and fungi at plant harvest were not observed. Moreover, when nutrients were added, the number of studied microorganisms significantly increased.Lengvai biodegradavimą pagerinančių pataisymų priemonių poveikis sunkiųjų metalų tirpumui ir akumuliacijai techniniuose pasėliuose – lauko bandymaiSantrauka. Dirvožemio užterštumas sunkiaisiais metalais yra dažna aplinkos problema visame pasaulyje. Inicijuotas fitoekstrakcijos procesas augaluose gali perkelti į jų antžeminius audinius dideles teršalų koncentracijas. Kadangi kai kurie sunkieji metalai dažniausiai esti netirpios būsenos, reikia pritaikyti chelatų agentus. Į kukurūzus buvo įterpta rizosfera (var. Kneja 530) ir saulėgrąžos (var. Favorit) EDDS bei NTA 1 ir 5 mmol–1 ir 5 g kg–1 mineralinių medžiagų, padidinant kadmio, švino ir cinko akumuliuotas koncentracijas. Ekstrahuotos CaCl2 metalo frakcijos padidino chelatų koncentracijos didėjimą. Tai pasireiškė visiems metalams, apdorotiems su NTA, ir švinui, paveiktam su EDDS. Visuose eksperimentuose akumuliuoto sunkiojo metalo koncentracijos buvo daug didesnės nei kontroliniame bandinyje. Vadinasi, didesnės NTA ir EDDS koncentracijos atveju akumuliuotas Cd saulėgrąžos lapuose buvo 3 kartus didesnis. Didžiausia Pb akumuliacija miežių lapuose išmatuota, pridėjus mineralinių medžiagų (62 mg kg–1). Kita vertus, neigiamas chelatų agentų naudojimo poveikis dirvožemio bakterijoms ir grybeliams augalų derliuje nebuvo nustatytas. Be to, kai buvo pridėta mineralinių medžiagų, padaugėjo nagrinėjamų mikroorganizmų.Reikšminiai žodžiai: sunkieji metalai, fitoekstrakcija, kviečiai, saulėgrąžos, EDDS, NTA, lauko bandymai, rizosferos mikroorganizmai.Полевые испытания влияния мер, способствующих деградации тяжелых металлов, их разложению и накапливанию в технических посевахРезюме. Загрязнение почв тяжелыми металлами – наиболее часто отмечаемая проблема во всем мире. Инициированный процесс фитоэкстракции в растениях может способствовать переносу значительных концентраций загрязнителей в их поверхностные ткани. В связи с тем, что некоторые тяжелые металлы находятся в нерастворенном состоянии, необходимо применение агентов хелатов. В настоящем исследовании в кукурузу была введена ризосфера (вар. Kneja 530) и подсолнечник (вар. favorit) EDDS и NTA 1 и 5 ммоль–1 ir 5 г кг–1 минеральных веществ для увеличения аккумулированных концентраций кадмия, свинца и цинка. Экстрагированные фракции металла CaCl2 способствовали увеличению концентрации хелатов. Это подтверждено исследованием всех металлов, подвергшихся воздействию NTA, и свинца, обработанного с помощью EDDS. Во всех экспериментах концентрации аккумулированного тяжелого металла были значительно больше, чем в контрольном образце. Следовательно, в случае большей концентрации NTA и EDDS содержание аккумулированного в листьях подсолнечника Cd было в три раза больше. Наибольшая аккумуляция Cd в листьях ячменя зафиксирована в случае добавления минеральных веществ (62 мг кг–1). Не было обнаружено и отрицательного воздействия от применения агентов хелатов на бактерии почвы и грибки в урожае растений. Кроме того, в результате добавления минеральных веществ количество исследуемых микроорганизмов увеличилось.Ключевые слова: тяжелые металлы, фитоэкстракция, ячмень, подсолнечник, NTA, EDDS полевые испытания, микроорганизмы ризосферы.First Published Online: 14 Oct 2010